The Relationship Of Fast Food Consumption Habits And Stress With The Menstrual Cycle Of Adolecence Woman In Senior High School N. 1 Gunungsitoli - Jernihati Krisniat Harefa (CV. AFDIFAL MAJU BERKAH, 2024)
Adolescence is the transition from childhood to adulthood. This transition is referred to as the maturation phase characterized by certain hormonally influenced changes. To find out the relationship of fast food consumption habits and stress with the menstrual cycle of young women in senior high School N.1 Gunungsitoli. This research uses an analytical type of research with a cross-sectional design. There are 79 girls in class X and XI. Using pss-10 questionnaire, food frequency questioner (FFQ) and menstrual cycle questionnaire. Using univariate analysis and bivariate analysis. The majority of young women in N.1 Gunungsitoli senior high school often eat fast food (53,2%). The majority of young women in N.1 Gunungsitoli senior high School experience moderate stress. The menstrual cycle of young women in N.1 Gunungsitoli senior high School experiencing abnormal cycles (65,8%). There is a significant relationship between the consumption habits of fast food and the menstrual cycle with a p-value of 0,000 (p-value ≤ 0,05). There is a relationship between stress levels and the menstrual cycle with a p-value of 0,028 (p-value ≤ 0,05). There is a relationship of fast food consumption habits and stress to the menstrual cycle.